2021
DOI: 10.1515/opag-2021-0043
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation ofMoringa oleiferaleaves powder in mutton patties: Influence on nutritional value, technological quality, and sensory acceptability

Abstract: Meat is a highly nutritious food rich in protein, fat, vitamins, and minerals. Nevertheless, chemical reactions and microorganisms might affect the quality of nutritional constituent of meat products. This study investigated the influence of adding Moringa oleifera leaves powder (MOLP) on the nutritional, technological properties, and consumer acceptability of mutton patties. Four treatments of mutton patties with 0, 0.3, 0.6, and 0.9% of MOLP were produced. The prepared patties (raw and cooked) were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
5
0
1
Order By: Relevance
“…Several studies have shown different results from this study. The cooking losses and WHC values increased compared to the control with the addition of up to 0.9% moringa flour, but the pH level increased by 0.9% in cooked mutton patties [22]. The utilization of moringa leaf extract on mutton patties stored for 0 days resulted in a pH value that was not differ from the control at levels up to 2%, but decreased at 3 and 5%.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Several studies have shown different results from this study. The cooking losses and WHC values increased compared to the control with the addition of up to 0.9% moringa flour, but the pH level increased by 0.9% in cooked mutton patties [22]. The utilization of moringa leaf extract on mutton patties stored for 0 days resulted in a pH value that was not differ from the control at levels up to 2%, but decreased at 3 and 5%.…”
Section: Resultsmentioning
confidence: 76%
“…[8] suggested the addition of 6% moringa seed flour to still maintain consumer acceptance. Besides, using moringa leaf meal up to 0.8% from total meat used [9] or processing cooked goat meat patties containing leaf flour up to 0.9% of the total meat used [11] have been performed and revealed its positive effect. Furthermore, other researchers reported the utilization of moringa leaf extract flour up to a level of 5% for mutton patties [10] and 20% in chicken burgers [12].…”
Section: Introductionmentioning
confidence: 99%
“…Lungu and Afolayan (2022), in their study, revealed that the addition of 1% root powder of Moringa oleifera was acceptable by consumers compared to the leaf part and comparable to the control group without the inclusion of the plant. Khomola et al (2021) also reported that the addition of 0.3% of MOLP on mutton patty samples had high sensory acceptance (aroma, taste, appearance and overall acceptability) and they were comparable in terms of sensory evaluation to those of the control group without any MOLP inclusion. In the study by Moyo et al (2014), goat meal supplemented with a blend of sunflower (170 g) and MOLP (200 g) leaf diet had a positive influence on consumer sensory ratings of goat meat with greater first bite, flavor, aroma and juiciness ratings in comparison to the group that was not supplemented.…”
Section: Influence Of Meat Fortification With Moringa Oleifera Lam An...mentioning
confidence: 84%
“…Marinasi daging sapi bali dengan ekstrak daun kelor, et al, 2015). Menurut Khomola et al (2021) tingginya protein disebabkan pengaruh dari senyawa fenolik dalam bubuk kelor karena ekstrak tanaman atau dalam hal ini kelor memiliki efek perlindungan terhadap denaturasi protein terhadap produk olahan daging. melaporkan bahwa penggunaan 0,4% bubuk kelor dapat meningkatkan kadar protein daging sapi giling (ground beef) selama penyimpanan suhu dingin, lebih lanjut dikatakan bahwa bubuk kelor merupakan sumber yang sangat baik dari semua asam amino yang merupakan bahan penyusun protein.…”
Section: Hasil Dan Pembahasanunclassified